Analysis of Service Quality on Competitiveness Improvement Strategies in XYZ Tutoring - Fikrul Gifar; Hartoyo Hartoyo; Asep Taryana (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Education has a strategic role in improving the quality of human resources, both through formal and non-formal channels. One form of non-formal education that is growing rapidly is tutoring, which functions to support students' academic readiness, especially in facing university entrance selection. Increasingly fierce competition requires tutoring institutions to provide quality services to be able to meet the needs of students and remain competitive. This study aims to analyze the influence of service quality on the strategy to increase the competitiveness of Bimbel XYZ using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) approach. The data was collected through an online questionnaire which was distributed to 115 grade 12 students from eight branches of Bimbel XYZ in the Bekasi and Cibubur areas. The results of the study show that the quality of service has a significant effect on increasing the competitiveness of XYZ tutoring. Service quality dimensions such as reliability, responsiveness, physical evidence, assurance, and empathy have been shown to contribute strongly in shaping a positive perception of service. In addition, customer satisfaction mediates the influence of service quality on competitiveness. These findings affirm the importance of continuous improvement of service quality as the main strategy to strengthen the competitive position of tutoring institutions in the midst of the dynamics of the non-formal education industry.